On the Price of Recreation Goods as a Determinant of Male Labor Supply - González‐Chapela, Jorge (Journal of Labor Economics, 2007)
We examine whether and how variations in the price of recreation goods influence men’s allocation of market work. For the United States, individual‐level data are combined with metropolitan‐area‐level price indices to estimate the male elasticity of intertemporal substitution of market work with respect to the price of recreation goods, which is found around 0.16 and statistically significant. The allocation of market work in response to changes in the price of recreation goods would create movements in the output of an economy. Moreover, it could contribute toward explaining the emerging differences in work and leisure between the United States and Europe.